SISTEM REKOMENDASI PADA PENGEMBANGAN SITUS E-COMMERCE UNTUK PENINGKATAN KEPUASAN PENGGUNA STUDI KASUS SEPATUMURAH.COM - AKHMADD DHARMA KASMAN (Paradigma, 2015)
Sepatumurah.com sites engaged in e-commerce-based footwear sales. This research aims to develop the site sepatumurah.com with a system of recommendation to assist the user in this case is the potential buyer to decide what items will be purchased through personalized services. The absence of interaction between the sites sepatumurah.com format with users or customers good today, so it is difficult to know the response users or customers will be offered product. The need for the development of e-commerce that existed previously to increase user satisfaction. Research has been done related to the development of applications with and the level of user satisfaction. Where the management aspects, aspects of the systems and aspects of further research into the implications of the results of this research..